Extension of method of moment equation to nonlinear deterministic vibrations - Anh, Nguyen Dong; Hai, Ninh Quang (Vietnam Journal of Mechanics, 2002)
The paper present the so-called "an extended averaged equation approach" to the investigation of nonlinear vibration problems. The numerical results in analysing the vibration systems with weak, middle and strong non-linearity show the advantages of the method.